Gender effects in the battle of the sexes: A tale of two countries - Adriani, Fabrizio; Pompeo, Monika; Sonderegger, Silvia (Journal of economic behavior & organization, 2022)
In a setting where inequality is ingrained and largely unavoidable (battle of the sexes), we investigate whether subjects condition their behavior on the gender of their opponent. In order to identify the role of culture and gender norms, we run the experiment in two countries, Norway and India, characterised by very different levels of gender inequality. Our evidence is consistent with different patterns of gender effects in the two countries. In India, subjects appear to become more ‘hawkish’ when facing a woman. This occurs only for lower education subjects and is observed primarily in female participants. Highly educated Indian participants do not discriminate between male and female opponents. In Norway, the data hint at a gender effect that is the opposite of what observed in India: it is present only in highly educated male participants, and takes the form of subjects appearing to become more ‘hawkish’ when facing a man. Our evidence suggests that these gender effects may be due to subjects experiencing different levels of inequality aversion depending on the gender of their opponent, in a manner that is mediated by their culture and gender norms.